Hemophilia Gene Therapy: Approaching the First Licensed Product - Paul Batty; David Lillicrap (HemaSphere, 2021)
The clinical potential of hemophilia gene therapy has now been pursued for the past 30 years, and there is a realistic expectation that this goal will be achieved within the next couple of years with the licensing of a gene therapy product. While recent late phase clinical trials of hemophilia gene therapy have shown promising results, there remain a number of issues that require further attention with regard to both efficacy and safety of this therapeutic approach. In this review, we present information relating to the current status of the field and focus attention on the unanswered questions for hemophilia gene therapy and the future challenges that need to be overcome to enable the widespread application of this treatment paradigm.